THE INFLUENCE OF NUTRITION EDUCATION AND REPRODUCTIVE HEALTH ON THE KNOWLEDGE OF TEENAGERS IN BANGUN VILLAGE REJO TANJUNG MORAWA DISTRICT KABUPATEN DELI SERDANG YEAR 2025 - Sinaga, Asnita; Simbolon, Rolasnih Lilista; Sitorus, Rumondang; Pasaribu, Riska Susanti (Yayasan Nuraini Ibrahim Mandiri, 2025)
Background: Adolescents are an age group that is prone to various health problems due to a lack of knowledge about nutrition and reproductive health. The rapid physical, psychological, and social changes of adolescence require a good understanding of these two important aspects. This study aims to determine the influence of nutrition and reproductive health education on the level of knowledge of adolescents in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency. Methods: The study used a pre-experimental design with a one group pretest-posttest approach. The sample consisted of 30 adolescents who were selected purposively. The main instrument was in the form of a multiple-choice questionnaire consisting of 20 questions. Data were collected through a pretest, an educational intervention for two sessions, and a posttest three days after the intervention. Data analysis using the Wilcoxon test showed that there was a significant increase in adolescents' knowledge after being educated (p < 0.05). Results: These results show that nutrition and reproductive health education is effective in improving adolescent knowledge. This study recommends that educational institutions and health services continue to integrate adolescent health education programs as part of preventive efforts against nutrition and reproductive health problems. Conclusion: Nutrition and reproductive health education significantly increases the knowledge of adolescents in Bangun Rejo Village. This educational intervention has proven to be effective as a preventive effort in forming healthy living behaviors from an early age.